Where infrastructure alone is not enough: developing well-functioning non-motorized transport with a focus on cycling in the 'Northern-Inner' district of Cape Town - Campbell, Dylan (School of Architecture, Planning and Geomatics, 2017)
Post-apartheid Cape Town is characterized largely by a sprawling and inequitable city form. Well-located land within the city tends to be expensive, and as a result the majority of poor residents have to travel long and time-consuming distances to employment opportunities, often spending close to half their monthly income on commuting. Current development patterns largely perpetuate this situation. Whilst non-motorized transport (NMT) often presents as a potentially equitable and efficient form of mobility, the context of long distance commuting coupled with a lack of NMT-specific connected infrastructure within metropolitan Cape Town is not conducive to NMT. The challenges and corresponding Interventions required to enable wellfunctioning NMT within cities broadly, and within the City of Cape Town in particular were explored through a variety of literature drawing on precedent from around the world, a review of NMT-related policy, and interviews with city officials and NGOs involved in promoting NMT. These challenges and interventions were then investigated in a particular context, namely the 'Northern inner' district of Cape Town, whereafter specific interventions were proposed. Key findings regarding the implementation of well-functioning NMT (and cycling in particular) indicate that there are a number of interconnected factors that need to be considered beyond the provision of NMT-specific infrastructure. At the metropolitan level, by developing high-density affordable housing opportunities in well-located areas, more compact environments with increased proximity between origins and destinations can be created. Such environments are far better suited to NMT. This can in turn begin to address the inequitable and inefficient current city form. NMT-specific infrastructure is of course very important in all NMT-enabling development (and particularly for cycling), and as such the equitable provision of NMT-prioritized intersections, paths and lanes in relation to infrastructure for motorized transport are very important. Finally, intermodal linkages between NMT and public transport, crime reduction through strategic placement and design of NMT infrastructure, and promotion of visibility and awareness of the value of NMT through public awareness campaigns constitute broader required interventions to enable well-functioning NMT. Regarding implementation, given the multiple interconnected factors involved in creating well-functioning NMT, it is important that the proposed interventions take place simultaneously, through an integrated inter-departmental approach.